2012
DOI: 10.1007/s00125-012-2486-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diabetes risk and admixture in postmenopausal African-American and Hispanic-American women

Abstract: Aims/hypothesis Type 2 diabetes is more prevalent in African-Americans (AFAs) and Hispanic-Americans (HAs) than in European-Americans. We assessed whether continental admixture was correlated with diabetes risk in these high-risk groups. Methods We estimated the proportion of sub-Saharan African (AFR), Amerindian (AMI) and European admixture using 92 ancestry-informative marker genotypes in 16,476 AFA and HA women from the Women's Health Initiative. Cox regression models were used to examine the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
5
32
0
1
Order By: Relevance
“…In our unadjusted estimates of the effect of BGA we found that having 100% African ancestry versus 100% European ancestry conferred a 1.5 fold risk of T2DM. Due to the conflicting findings regarding BGA to date, the finding that socioeconomic status explains a large proportion of this association agrees with some studies [29, 30, 32] but is in contrast with others [6, 31, 32]. …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our unadjusted estimates of the effect of BGA we found that having 100% African ancestry versus 100% European ancestry conferred a 1.5 fold risk of T2DM. Due to the conflicting findings regarding BGA to date, the finding that socioeconomic status explains a large proportion of this association agrees with some studies [29, 30, 32] but is in contrast with others [6, 31, 32]. …”
Section: Discussionsupporting
confidence: 86%
“…While BGA and race/ethnicity are constant, the effects of socioeconomic and lifestyle/behavioral factors may be fine-tuned in a proportional hazards regression model. However, our study does provide evidence for a temporal effect between SES and diabetes incidence whereas many studies of BGA have been limited to cross-sectional [6, 30, 31] or limited measures of SES [3032]. Finally, although the sample is geographically limited to Boston, Massachusetts, the BACH Survey sample has been compared to other large regional (Behavioral Risk Factor Surveillance System) and national (the National Health and Nutrition Examination Survey) on a number of socio-demographic and health-related variables.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Many factors have been identified as contributing to these disparities (4), including variations in lifestyles and behaviors, biophysiological, psychosocial, sociodemographic, and environmental factors and biogeographic ancestry (BGA) (5,6). Research to date, however, has largely focused on individual risk factors in isolation, and the relative contribution of these influences have not been identified (4).…”
Section: Introductionmentioning
confidence: 99%